Higher order thalamic nuclei resting network connectivity in early schizophrenia and major depressive disorder. (28th February 2018) - Penner, Jacob; Osuch, Elizabeth A.; Schaefer, Betsy; Théberge, Jean; Neufeld, Richard W.J.; Menon, Ravi S.; Rajakumar, Nagalingam; Bourne, James A.; Williamson, Peter C.
Abstract: The pulvinar and the mediodorsal (MDN) nuclei of the thalamus are higher order nuclei which have been implicated in directed effort and corollary discharge systems. We used seed-based resting fMRI to examine functional connectivity to bilateral pulvinar and MDN in 24 schizophrenic patients (SZ), 24 major depressive disorder patients (MDD), and 24 age-matched healthy controls. SZ had less connectivity than controls between the left pulvinar and precuneus, left ventral-lateral prefrontal cortex (vlPFC), and superior and medial-frontal regions, between the right pulvinar and right frontal pole, and greater connectivity between the right MDN and left dorsolateral prefrontal cortex (dlPFC). SZ had less connectivity than MDD between the left pulvinar and ventral anterior cingulate (vACC), left vlPFC, anterior insula, posterior cingulate cortex (PCC), and right hippocampus, between the right pulvinar and right PCC, and between the right MDN and right dorsal anterior cingulate (dACC). This is the first study to measure the functional connectivity to the higher order nuclei of the thalamus in both SZ and MDD. We observed less connectivity in SZ than MDD between pulvinar and emotional encoding regions, a directed effort region, and a region involved in representation and salience, and between MDN and a directed effort region. Highlights: Higher order thalamic nuclei networks studied in schizophrenia and depression. Connectivity deficits to directed effort regions found in schizophrenic patients. Increased connectivity to motor/somatosensory areas not confirmed.